KONSEP LABA AKUNTANSI SYARIAH DALAM BISNIS SYARIAH DI INDONESIA - Sa’diyah, Hikmatus; Latifah, Eny (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2023)
The purpose of this research is to examine the concept of the benefits of Islamic accounting for Islamic businesses in Indonesia. The role of the Islamic accounting concept of profit is crucial ensuring fairness, transparency, and compliance with sharia principles in business management. This article will discuss how these concepts are applied, how they impact financial transparency, and how they relate to Islamic values. The concept of Islamic accounting profit refers to the measurement and reporting of profit in accordance with the principles of Islamic sharia. Profits earned from Islamic businesses must be halal and not violate religious law. The purpose of this study is to increase our understanding of the ideas of Islamic accounting profit, why it is important to be applied in Islamic business, and the difficulties and opportunities that arise when applying it. The research method used is to conduct literature research by collecting data from relevant articles, books, and journals. The concept of Islamic accounting profit in Islamic business has several advantages. These include emphasizing social and environmental responsibility, encouraging sustainable investment, increasing trust and transparency, and conforming to Islamic values.